How the COVID-19 Overcomes the Battle? An Approach to Virus Structure (Iranian Journal of Kidney Diseases, 2020)
Coronaviruses primarily cause zoonotic infections, however in the past few decades several interspecies transmissions have occurred, the last one by SARS-CoV-2, causing COVID-19 pandemic, posing serious threat to global health. The SARS-CoV-2 spike (S) protein plays an important role in viral attachment, fusion and entry. However, other structural and non-structural SARS-CoV-2 proteins are potential influencers in virus pathogenicity. Among these proteins; Orf3, Orf8, and Orf10 show the least homology to SARSCoV proteins and therefore should be further studied for their abilities to modulate antiviral and inflammatory responses. Here, we discuss how SARS-COV-2 interacts with our immune system.